News: Kassala Is Dying: Challenges of Healthcare in Sudan - Ibrahim, Eyad (Trinity Student Medical Journal, 2018)
Sudanese doctors working in Ireland detailed their knowledge and experience of medicine in Sudan and highlighted the current chikungunya epidemic in Kassala in a novel event organized by the Trinity Chapter of the Association of Medical Students Ireland (AMSI TCD) earlier this month. The panel based discussion mediated by AMSI Local Officer Eyad Ibrahim included four expert doctors, Dr. Amin Amin, Dr. Nemer Osman , Dr. Hatim Ibrahim, and Dr.Ismail Mohammed. The doctors, representing the group Sudanese Doctors in Ireland (SDI), spoke about global health, medical inequality and the tumultuous political climate in Sudan to an audience of largely medical students. Dr. Amin, an orthopaedic surgeon at Connolly Hospital Blanchardstown, introduced both the talk and the harrowing ongoing situation in Kassala. Specifically, he raised concern about the rapid outbreak of the mosquito borne virus chikungunya. “Everybody has it and you won’t find another man, woman or child who doesn’t,” he said emphatically. In a melancholic tone, he described that the treatment for this infection was supportive management such as intravenous fluids and paracetamol — resources readily available in any Irish hospital, but lacking in Kassala and Sudan in general. With proper treatment, only those vulnerable with pre-existing conditions such as diabetes, frailty, or co-infection with other viruses such as Zika, would suffer debilitating morbidity or death. Most would fully recover with symptoms mainly comprising fever and joint pain. However, the lack of governmental aid and recognition of this crisis have resulted in more severe widespread consequences. “The town stops, farmers don’t work, teachers won’t show up at school, it’s more morbidity than mortality,” Dr. Amin said. The latest report by the Central Sudanese Doctors’ Committee reported over 16,000 infections and 45 deaths due to chikungunya. In response, the 600 Sudanese doctors currently in Ireland have spread the tragic tweet #KassalaisDying in solidarity with the social media campaign aiming to raise awareness. The campaign reflects that in addition to people literally dying from this infection, the magnitude of debilitation is grinding the city to a halt. In addition, panelists discussed interesting differences of healthcare management in Sudan. These included more realistic aspects of tropical diseases such as malaria and dengue fever. Dr. Ibrahim, consultant endocrinologist working in Ulster Hospital in Belfast, recalled a few insightful examples. While working in the White Nile Estate near Khartoum in Sudan as an SHO in 1991, a lady presented to hospital with fits due to eclampsia. Dr. Ibrahim was required to deliver the baby with the help of only a few nurses. “We had to use an oven to sterilize the equipment, we had to be our own surgeon and anesthesiologist,” he said. Dr. Ibrahim recalled that the completely healthy woman returned to the hospital a few days later for a check up, thanking him for the help, however he reminded the audience that happy endings like this were not always the case. He went on to describe the challenges of the practical aspects of managing mosquito-borne pathologies other than chikungunya. One recommendation to prevent illness is to use bulky full-body suits for outdoor occupations. “Realistically, no one is going to wear a huge suit, if they’re too poor and they can’t afford it, they are just going to go out into the fields to work in order to feed their children,” he said. He added that infection from mosquitoes is an around the clock threat, with lower socioeconomic groups in Sudan at the highest risk. Dr. Nemer, consultant oncologist in Limerick Regional Hospital, went further to discuss low cost methods of diagnostics that are necessary with scarce resources. He said that it was common to use vinegar to locate lesions of cervical cancer caused by HPV, a problem routinely screened for by Pap smears in Ireland, but a more widespread and devastating situation for women in Sudan. “In the East, you can’t do these fancy tests and biomarkers, you have to use what we had, and what we had is vinegar,” said Dr. Nemer. Another aspect raised was the turbulent political climate of Sudan. The doctors suggested that funding was directed towards benefiting government officials resulting in resources taken away from healthcare. “People like to spend money on things that matter most to them. Here in the West, the government likes to spend money on health and education,” said Dr. Amin. “However, in Sudan, the government likes to spend money on military and security.” Activists have criticized the delay in the government’s response to the situation in Kassala, which had a significant impact on the situation in the region. The delay was significant enough for the infection to spread from a small number of 30-40 people to the whole region of Kassala and other areas like Port Sudan. Currently, the number of infected people is around 16,000. The spread to other areas was facilitated by fear in the region that resulted in dispersion, as well as heavy rains allowing for the mosquito vector to travel. Factors such as patient education, treatment and quarantine availability as well as lack of transport and infrastructure added to the severity. Speaking about the healthcare challenges in developing countries such as Sudan, Dr. Ibrahim stated that the lack of medical diagnostic resources necessitates developing better clinical skills. In his practice in Ireland, he pointed out that he finds some tests that are ordered here can be unnecessarily excessive. “Some of the investigations we do here are very wasteful, and our clinical skills are not being developed to their potential. I encourage my juniors to use their clinical skills rather than rely on unneeded diagnostic tests…in Sudan the better clinical skills are a necessity,” he said. Furthermore, Dr. Amin said that often times these investigations are done in order to avoid consequence of legal action. “Even though you know for certain a patient has a fracture from presentation, you will still X-Ray them. Even if it was subtle fracture you would put them in CT scanner head to toe,” he said. Dr. Ismail, consultant rheumatologist in Craigavon Hospital in Northern Ireland, simplified the striking difference in medicine practiced in Sudan and Ireland. “It’s non-comparable,” he said. The doctors offered electives in Sudan to medical students interested in experiencing medicine in a developing country and even offered to pay for some of the expenses such as accommodation and visas. “Both the students and the country benefits from people going over,” Dr. Nemer said as the event concluded. “Hopefully one day in the future Sudan will cease from being the hotbed of disease and illness that it is.” The audience was left with a quote by the great Sudanese writer Tayeb Salih. “Everyone starts at the beginning of the road, and the world is in an endless state of childhood.” With content from Dane Wanniarachige Students React to #KassalaisDying Event “When I first heard about the event I remember feeling a great deal of pride, being of Sudanese origins myself. Seeing Sudanese doctors in Ireland —which are not few— represented and given such a platform filled me with joy. But it was clear that this event was more than just Sudanese doctors talking about medicine. The event offered a unique and eye opening —as well as saddening— insight into the practice of medicine in under developed nations, the doctors experience in that regard formed a unique insight into what otherwise is a distant reality. In addition, I greatly enjoyed the rich information volunteered by the great practitioners who could at least be described as admirable. As a student I have benefited greatly from the event, both medically and in a humanitarian aspect, I look forward to continued contact with the organization throughout my medical career.” —Mawaheb Elnour, 1st Year Medical Student, Trinity College Dublin “As a student who isn’t born or raised in Sudan, I felt overwhelmed by discovering about the health-related predicaments that entail the daily lives of individuals in that country. I realized that while here in Ireland, we’re trying to find cures to big conditions such as cancer or cystic fibrosis, back in Sudan, something like malaria, something that people in Ireland are completely unaware of, is affecting myriads of helpless, innocent people daily. It made me question my duty as a future doctor and as a citizen to this world. It prompted me to ask myself, what am I doing to make even the slightest change for people who don’t deserve to lose their lives over conditions that do have a cure. This event opened my eyes to the reality and status of health-care in third world countries and it motivated me to take part in missions or projects that can help ease the health-related obstacles that nations such as in Sudan face.” —Iffah Khalid, 1st year Medical Student, Trinity College Dublin “I found the event really inspiring as it prompted us to consider the challenges faced by doctors in Sudan; not only during epidemics, but also in daily life with limited resources. Before the talk I had very limited knowledge on Sudan, but listening to the consultants and their passion for their the country made me want to find out more about Sudan and possibly visit in future! It was one of my favourite AMSI events so far, I’m looking forward to future events like it!” —Blaithin Thomasius, 3rd Year Medicine Student, Trinity College Dublin “I think it is a very innovative event by connecting with experienced practitioners. The speakers addressed some recent and concerning diseases, from which the students could gain valuable knowledge and critical thinking that are outside of the books. The speakers described the healthcare conditions in a developing setting and brought up political, financial and geographical aspects of the diseases.It was very interesting, even when I’m not from medical discipline.” —Yue Peng, Final Year Biochemistry Student, Trinity College Dublin